2008
DOI: 10.1242/jcs.020941
|View full text |Cite
|
Sign up to set email alerts
|

FAK, PDZ-RhoGEF and ROCKII cooperate to regulate adhesion movement and trailing-edge retraction in fibroblasts

Abstract: A key step in cell migration is the dynamic formation and disassembly of adhesions at the front and the concomitant movement and release of adhesions in the rear of the cell. Fibroblasts maintained in the absence of serum have stable adhesions within the rear of the cell and exhibit reduced trailing-edge retraction resulting in an elongated cell phenotype. Addition of lysophosphatidic acid (LPA) induced the movement of adhesions and retraction of the trailing edge, thus mimicking tail retraction in a migrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 41 publications
10
94
1
1
Order By: Relevance
“…RhoA drives cell migration in part by stimulating actomyosin contraction, which in the rear of the cell results in disassembly of focal adhesions and retraction of the trailing edge. Lack of trailing edge retraction classically results in long extensions in the rear of the migrating cell (31,35,36). To monitor the contribution of each Net1 isoform to trailing edge retraction, we assessed the effects of their knockdown on cells migrating into a cleared area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RhoA drives cell migration in part by stimulating actomyosin contraction, which in the rear of the cell results in disassembly of focal adhesions and retraction of the trailing edge. Lack of trailing edge retraction classically results in long extensions in the rear of the migrating cell (31,35,36). To monitor the contribution of each Net1 isoform to trailing edge retraction, we assessed the effects of their knockdown on cells migrating into a cleared area.…”
Section: Resultsmentioning
confidence: 99%
“…This value was then divided by the width of the cell in the nucleus, perpendicular to the first axis (31). For analysis of FAK activation after wounding or replating, images were acquired with a constant exposure time, and the background subtraction was performed uniformly for all samples and time points.…”
mentioning
confidence: 99%
“…Notably, early work suggested that the primary action of RhoA was to mediate trailing edge retraction in migrating cells (58). In accordance with these concepts, PDZ-RhoGEF operates preferentially at the rear of migrating cells to activate Rho and promote tail retraction in cooperation with ROCKII (20). However, studies using a fluorescence resonance energy transfer reporter for assessing RhoA activity demonstrated that RhoA activity is found at the leading edge (24,40).…”
Section: Discussionmentioning
confidence: 95%
“…GEF-H1 activation, however, is less likely to contribute to the force-induced RhoA activation per se, because RhoA activity still increases upon force application when MT dynamics are inhibited by taxol. Other guaninenucleotide exchange factors (GEFs), such as p190RhoGEF and PDZ RhoGEF, that localise to FAs and are involved in regulating RhoA activity (Iwanicki et al, 2008;Lim et al, 2008;Tomar and Schlaepfer, 2009) might be potential candidates with respect to the reorganisation of FAs and the upregulation of RhoA activity upon stretching forces.…”
Section: Discussionmentioning
confidence: 99%